Revestimento comestível contendo natamicina e cloreto de sódio para controle de fungos em queijo minas cura - Vollbrecht, Chrislayne Pais (2023)
Cheese is considered one of the most consumed foods in Brazil, with different types. Maturation and storage can become conducive to the proliferation of deteriorating microorganisms, such as molds and yeasts, which considerably harm the product and bring economic losses to the food industry. Edible coatings with the addition of the antimicrobial agent natamycin can increase preservation efficiency against these microorganisms both during maturation and storage. Natamycin, classified as a polyene macrolide, when applied, irreversibly binds to ergosterol, acting to control fungal growth. The objective of this work was to develop an edible coating containing natamycin and sodium chloride to control fungi in Minas Cura cheese. Initially, the fungus developed in cheeses in the maturation chambers was isolated, and the antimicrobial activity of natamycin was verified by the minimum inhibitory concentration in the isolate. The fungal cheese isolate was identified as belonging to the genus Penicillium due to its macro and micromorphological characteristics, and natamycin showed between the tested concentrations (256, 128, 64 and 32 μg/mL) in PDA medium, MIC of 128 μg/mL. Filmogenic solutions of sodium caseinate were prepared, with plasticizer glycerol and sodium chloride (NaCl) with natamycin added at 500 μg/mL. The films were prepared by film casting to be characterized, performing test formulations both with the addition of Natamycin, Sodium Chloride and Sodium Caseinate. The puncture force was evaluated, which indicated a significant effect of the presence of NaCl reducing the mechanical resistance. This also demonstrated the effect of increasing the water vapor permeation and solubility of the films. Natamycin had no effect on these parameters. Fourier Transform Infrared Spectrophotometry (FTIR) was performed to verify the interactions between natamycin and the other components of the film, highlighting the interaction between the hydroxyl and ether groups by coordination complexes with sodium ions. With X-Ray Diffraction analysis it was determined that natamycin is in an amorphous state in the films, and the only crystallinity identified was that of NaCl. The verification of color and texture during the shelf life of the samples with and without the filmogenic solution, showed that over the storage time, the trend is equal to the control treatment. As for the microbiological count of molds and yeasts, during all months it presented lower values for the cheese involved by the coating containing the antifungal. However, both samples showed increasing counts for yeast results. It can be concluded that the application of an edible coating containing natamycin to control the proliferation of fungi during the maturation of Minas Meia Cure cheese obtained satisfactory results in their evaluated parameters.